Successful management of pelvic bleeding after caesarean hysterectomy by means of Foley catheter-condom balloon tamponade - Atilgan, Remzi; Aslan, Kubat; Can, Behzat; Sapmaz, Ekrem (BMJ Publishing Group, 2014)
In this case report, we describe a 28-year-old woman with multipar gestation who developed postcaesarean atonia and severe pelvic haemorrhage which continued in spite of peripartum hysterectomy. A balloon tamponade tool was formed with Foley catheter and a condom, and was inserted into the pelvis through the vaginal cuff. The tampon was inflated up to 2200 mL and the pelvic tamponade was applied and bleeding was controlled. On the patient's incapability of urination, the volume of condom was decreased to 1800 mL and urination was achieved. seventy-two h postoperatively the Foley catheter-condom was removed through an abdominal incision. Pelvic bleeding ceased. After monitoring for a week, no postoperative fever, infection, pelvic abscess and haematoma were observed. Use of Foley catheter-condom as a pelvis pressure tampon tool may be a simple and effective method which can be easily used to control pelvic bleeding. Copyright 2014 BMJ Publishing Group. All rights reserved.
Keywords: ampicillin; clindamycin; ergotamine; gentamicin; hemoglobin; misoprostol; oxytocin; adult; article; bleeding; case report; cauterization; cesarean hysterectomy; cesarean section; compression therapy; condom; cryoprecipitate; disease control; disease severity; erythrocyte transfusion; female; Foley balloon catheter; human; hysterectomy; massage; operative blood loss; ovariectomy; pelvic bleeding; pelvic disease; postoperative care; priority journal; reoperation; uterine atony; uterus contraction